EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR PENDIDIKAN IPA PADA PELAJARAN PANCASILA TENTANG CONTOH ATURAN DI RUMAH KELAS 1 SDN WEGOKNATAR - Fatima Peni Atulolong, Maria; Bera, Lukas; Kristiani Maria, Sonya (Universitas Cokroaminoto Palopo, 2024)
This study aims to determine the effectiveness of the use of the Role Playing learning model on the learning outcomes of Pancasila Education about examples of rules at home in grade 1 of SDN Wegoknatar. This type of research is an experimental research with Pre-Experimental designs with a One-Group Pretest-Posttest model. The sample in this study was all students of grade I of SDN Wegoknatar which amounted to 17 people and consisted of 14 boys and 3 girls. The data collection techniques used in this study are direct observation and written test questions. The data analysis techniques used in this study are data from pretest and posttest results to compare averages, normality tests, hypothesis tests and N-Gain tests to determine the effectiveness of the use of the Role Playing learning model. From the results of data analysis, the average score obtained in the pretest was 55.5 to 78.3 in the posttest while the N-Gain was obtained with a value of 0.61 so it is a medium category. This means that the Role Playing learning model is effectively used and there is an influence of the use of the Role Playing learning model on the learning outcomes of Pancasila Education about examples of rules at home.